Political pluralism and governance challenges in Kuwait and Bahrain - (:unkn) unknown (My University, 2013)
Résumé de l'ouvrage : Governance in the Middle East and North African will be essential reading for scholars, activists and policy makers. This new Handbook presents the first comprehensive framework of the question of governance in the Middle East in its various forms and manifestations: political, economic, and government performance.This book is structured into two parts: Part I provides some theoretical background and analyzes the patterns and challenges of governance in the Middle East, providing some global context; Part II will examine specific cases in selected countries and regions in the Middle East and North Africa.This book is aimed at a wide audience. Policy makers, policy analysts, as well as journalists will benefit from the history and analysis presented in the book. Also, academics will find important material for research and class work. Professors teaching courses on US Foreign policy, Middle East, International Relations, Comparative Politics and many related fields will find the book a very suitable choice for their students to read. Given the media and general public’s interest in the Middle East and North Africa, it will also appeal to a wide range of educated readers in the USA, the United Kingdom and many other countries world-wide.
Keywords: African Research